Students' Comprehension of the Video “Was mach ich hier eigentlich? Die erste schriftliche Arbeit bestehen!” - Purwanti, Meriyani; Amanda Mayangsari; Danang Raif Abdunafi (Nexus Publishing NXP, 2025)
This study aims to compare students' comprehension of the video titled “Was mach ich hier eigentlich? Die erste schriftliche Arbeit bestehen!”. The research focuses on students' ability to understand video content through two primary skills: listening to audio and reading subtitles. A quantitative descriptive method with an experimental approach was employed. Primary data were collected through questionnaires and comprehension tests administered to 22 students enrolled in the “Wissenschaftliches Schreiben” class. The questionnaire measured students’ perceptions of comprehension, cognitive load, and the influence of audiovisual elements, while the comprehension test assessed their factual understanding of the video content and main message. Secondary data were obtained from books, scholarly journals, and relevant expert opinions. The findings discuss the comparison between listening and reading skills in comprehending video content, based on questionnaire analysis. The results contribute to the academic understanding of learning methods and provide recommendations for educators regarding students' preferences and the effectiveness of instructional strategies in the context of video-based learning.